2020
DOI: 10.3390/app10031061
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polymer Types on the Mechanical Properties of Polymer-Modified Cement Mortars

Abstract: This is an experimental study showing the effect of four types of polymers (acrylate polymer (AC), polyvinyl alcohol (PVA), styrene–butadiene rubber (SBR), and ethylene-vinyl acetate (EVA)) on the mechanical properties of polymer-modified cement mortars (PCMs). One polymer dosage was used in this study (3%), and the effect of this dosage on PCMs was compared with a control mortar mix with 0% polymer. The compressive, flexural, and pull-off bond strengths were measured and compared with previous results in work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 28 publications
0
12
1
1
Order By: Relevance
“…In studies under [4,5], comparisons involved various redispersed vinyl copolymer powders. In most contemporary papers [6][7][8][9][10][11][12][13][14], the authors identified three main additives: vinyl acetate/versatate copolymers (VA/VeoVa) and vinyl acrylic (VA Acrylic), as well as calcium formate powder (FormCa).…”
Section: Examined Materials and Equipment Used In Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies under [4,5], comparisons involved various redispersed vinyl copolymer powders. In most contemporary papers [6][7][8][9][10][11][12][13][14], the authors identified three main additives: vinyl acetate/versatate copolymers (VA/VeoVa) and vinyl acrylic (VA Acrylic), as well as calcium formate powder (FormCa).…”
Section: Examined Materials and Equipment Used In Experimentsmentioning
confidence: 99%
“…The authors of [9,10] mainly paid attention to the general characteristics of the effects of additives aimed more at affecting the mechanical characteristics, while only superficially describing the chemical effect of additives on the properties of mixtures.…”
Section: Examined Materials and Equipment Used In Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulgular, SBR ile modifiye edilen çözümlerin gelişmiş mekanik parametrelere, yani gelişmiş sızdırmazlığa ve donma etkisine karşı daha fazla dirence sahip olduğunu göstermiştir. SBR lateks içeren beton üzerinde birçok araştırma yapılmıştır [21][22][23]. Aşağıdaki paragrafta, SBR'nin çimentolu kompozitlerde kullanımına ilişkin bir literatür taraması sunulmaktadır.…”
Section: Introductionunclassified
“…Styrene-Butadiene Rubber (SBR) latex having characteristics of high-polymer dispersion emulsion and capable of bonding with other materials, is extensively used material in engineering construction. Many types of research have been carried out on concrete incorporating SBR latex [13][14][15]. In the following paragraph, a brief literature review concerning the use of SBR in cementitious composites is provided.…”
Section: Introductionmentioning
confidence: 99%